Pintura habitada : fotoperformance em Helena de Almeida - Vinhosa, Luciano (2018)
Based on the rupture of the illusionist space of representation, carried out by some artists in the 1960s, we arrive at the photographic series by Helena Almeida, Pintura habitada (1975), a performance designed for the photographic camera with ways to problematize the limits of painting. With this company, we intend to discuss the new statute of representation and the mimesis